Behavioral Law and Economics 2000
DOI: 10.1017/cbo9781139175197.007
|View full text |Cite
|
Sign up to set email alerts
|

Reluctance to Vaccinate: Omission Bias and Ambiguity

Abstract: Subjects are reluctant to vaccinate a (hypothetical) child when the vaccination itself can cause death, even when this is much less likely than death from the disease prevented. This effect is even greater when there is a 'risk group' for death (with its overall probability held constant), even though the test for membership in the risk group is unavailable. This effect cannot be explained in terms of a tendency to assume that the child is in the risk group. A risk group for death from the disease has no effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
313
0
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(333 citation statements)
references
References 3 publications
15
313
0
5
Order By: Relevance
“…Also, since it has been shown that actions are more likely to be associated with immoral acts (Ritov & Baron, 1990;Spranca, Minsk, & Baron, 1991), being asked to think about the consequences of one"s regrettable behaviours, which are likely to include feelings of guilt, shame or remorse, might actually inhibit the search for consequences of action regrets relative to inactions.…”
Section: Chapter Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, since it has been shown that actions are more likely to be associated with immoral acts (Ritov & Baron, 1990;Spranca, Minsk, & Baron, 1991), being asked to think about the consequences of one"s regrettable behaviours, which are likely to include feelings of guilt, shame or remorse, might actually inhibit the search for consequences of action regrets relative to inactions.…”
Section: Chapter Discussionmentioning
confidence: 99%
“…In health and medical contexts the prospect of regret has been shown to bias people"s judgement in decisions concerning both real (Asch et al, 1994;Meszaros et al, 1996;Ziarnowsky, Brewer & Weber, 2008) and hypothetical vaccinations Connolly & Reb, 2005;Ritov & Baron, 1990). The increasing involvement of patients in medical decision making is seen as a major source of potential regret (Brehaut et al, 2003) and the anticipation of regret is recognised as something likely to shape treatment choices.…”
Section: Anticipated Regretmentioning
confidence: 99%
“…The omission bias reflects a preference for inaction that results in a worse outcome rather than action that results in the same worse outcome. For example, subjects have revealed a preference for withholding vaccination for a child because the vaccination may itself cause the child's death, even if the risk of death from the prevented disease is even greater (Ritov and Baron, 1990). Andreoni's (1995) warm glow/cold prickle theory is a mirror image of the omission bias, a commission bias; a preference for action that results in a beneficial outcome rather than inaction that results in the same beneficial outcome.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, it might also be that action-orientedness is related to opportunity recognition or the tendency to exploit opportunities. For this reason, biases towards inaction are mostly studied in hypothetical settings (Ritov and Baron, 1990;Patt and Zeckhauser, 2000;Tanner and Medin, 2004). This does not often lead to findings that are relevant from an economic perspective because incentives are lacking.…”
Section: Introductionmentioning
confidence: 99%